2017
DOI: 10.1039/c7cc08270c
|View full text |Cite
|
Sign up to set email alerts
|

Half-sandwich ruthenium(ii) complexes containing N^N-chelated imino-pyridyl ligands that are selectively toxic to cancer cells

Abstract: Chemotherapy is limited by its poor selectivity towards cancer cells over normal cells. Herein, we designed half-sandwich ruthenium imino-pyridyl complexes [(η-bz)Ru(N^N)Cl]PF to achieve selective cytotoxicity to cancer cells. This kind of ruthenium complex has unique characteristics and is worthy of further exploration in the design of new anticancer drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 22 publications
2
64
0
Order By: Relevance
“…We have reported half‐sandwich iridium complexes containing N^N‐chelating iminopyridyl ligands that displayed highly potent antiproliferative activity against cancer cells, but poor cytotoxic selectivity between cancer and normal cells . Substitution of cyclopentadienyl iridium moiety with ruthenium benzene led to a decrease of potency but better cytotoxic selectivity, suggested that the metals play a vital role in anticancer activity. Probably the ruthenium analogues of the iridium complexes in this work can achieve selectivity at some levels, which would be interesting to study in future work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported half‐sandwich iridium complexes containing N^N‐chelating iminopyridyl ligands that displayed highly potent antiproliferative activity against cancer cells, but poor cytotoxic selectivity between cancer and normal cells . Substitution of cyclopentadienyl iridium moiety with ruthenium benzene led to a decrease of potency but better cytotoxic selectivity, suggested that the metals play a vital role in anticancer activity. Probably the ruthenium analogues of the iridium complexes in this work can achieve selectivity at some levels, which would be interesting to study in future work.…”
Section: Resultsmentioning
confidence: 99%
“…Organometallic transition metal‐based complexes exhibit a wide range of applications for the design of antitumor drugs due to their potential redox features, diverse structural types and varied ligand bonding modes . Organometallic complexes of the group VIIIB elements platinum, ruthenium, osmium, rhodium, palladium and iridium have received much attention as potential antitumor agents . Following the clinical success of platinum‐based antitumor drugs such as cisplatin, carboplatin and oxaliplatin, metal‐mediated antitumor drugs have attracted wide attention in chemotherapeutic research .…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of base pairs of DNA with complexes usually involves intercalation, interaction, non-intercalative electrostatic interactions as wella sd amage of the DNA double helix. [42][43][44][45] The change in the absorption wavelength of the as-synthesized complexes as the amount of CT-DNA (DNA sodium from calf thymus) increased was determined by means of UV/Vis titration, and the bindingc onstants( K b )o ft he complexes were also calculated. The role of metal iridium in our complexes is probablyt op rovideacoordination center.…”
Section: Interaction With Ct-dnamentioning
confidence: 99%
“…However, similar to other cytotoxic drugs, problems of platinum‐based anticancer drugs, normal tissue toxicity, and drug resistance limit their future use . These factors necessitate the exploration of new chemotype anticancer agents that have metal and new mechanisms of action different from platinum …”
Section: Introductionmentioning
confidence: 99%